NEUROCHEMICAL ASSESSMENT AND BEHAVIORAL ROLE OF TUBEROINFUNDIBULAR PEPTIDE-39 IN ACUTE RESTRAINT STRESS-INDUCED DEPRESSION IN RATS. - V, Sankar; M, Ramanathan; G, Venkatesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Tuberoinfundibular peptide of 39 (TIP39) is a potent agonist to the parathyroid hormone 2 receptor (PTH2R) abundantly expressed in brain. The current study focused to evaluate the role of TIP39 in acute restraint stress (ARS)-induced depression model. Methods: Rats were exposed to ARS for 2 h to establish the depression and then subjected to open field and forced swim test (OFT and FST). TIP39 (1 and 10 nmol/rat) and HYWH (1 nmol/rat) are a PTH2R antagonist which was infused through intracerebroventricular route. Diazepam (2 mg/kg, i.p) was utilized as reference standard. Results: The results depict ARS significantly diminished the TIP39 expression in cerebral regions and causes depression-like behavior. TIP39 significantly decreased the immobility period in FST. In the OFT, TIP39 significantly increased the ambulatory activity and did not alter the rearing and grooming activity in comparison to ARS group. After TIP39 treatment, plasma noradrenaline levels were significantly increased, whereas the serotonin levels were unaltered. The corticosterone levels also decreased significantly. In rat brain tissues, TIP39 significantly reversed the abnormalities in glutamate and gamma-aminobutyric acid (GABA) level by ARS induction. In contrast, HYWH-treated rats did not show any significant variations in the neurochemical and behavioral parameters in comparison to ARS rats. Conclusion: Our reports submitted that the primary evidence depicting the stimulation of TIP39 expression could modulate the monoaminergic, GABAergic, and glutaminergic release with the support of hypothalamic-pituitary-adrenal axis that can be produced an antidepressant-like effect evident with the interactive study.